CONSERVATION BASED INTERACTIVE MULTIMEDIA DEVELOPMENT IN CLASS IV IPS CONTENTS - Ramandhani, Rovi; Widihastrin, Florentina (Universitas Negeri Semarang, 2020)
This research is aimed at developing adobe flash interactive multimedia based on conservation on the social studies subject in fourth graders of Purwoyoso 03 Elementary School. Based on pre-research data through interviews, observations, and documents, in Purwoyoso 03 Elementary School there are problems found in social studies learning related to limited learning media, students only utilize media in the form of images and daily objects like a map image without having any other supporting media. This type of research was Research and Development (RD) by Borg Gall which is adapted by Sugiyono in 8 steps, namely: (1) potential and problems; (2) data collection; (3) product design; 4) design validation; (5) design revisions; (6) product trials; (7) product revisions; (8) trial use. The results showed that the development of adobe flash interactive multimedia based on conservation was very feasible; 82.81% feasibility of presentation by media experts, the eligibility of content by material experts at 96.87%, and the feasibility of language by linguists at 82.81%. The average difference test result using the t test showed the sig. (2-tailed) value is 0.000 0.050 which means there were significant differences between the pretest and posttest learning outcomes. The average increase (N-gain) of the pretest and posttest result was 0.385 with moderate criteri The average difference test result using the t test showed the sig. (2-tailed) value is 0.000 0.050 which means there were significant differences between the pretest and posttest learning outcomes. The average increase (N-gain) of the pretest and posttest result was 0.385 with moderate criteri The average difference test result using the t test showed the sig. (2-tailed) value is 0.000 0.050 which means there were significant differences between the pretest and posttest learning outcomes. The average increase (N-gain) of the pretest and posttest result was 0.385 with moderate criteri.